A Comprehensive Review on the Progress of Coagulation for Natural Organic Matter Removal in Water Treatment (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2023)
Natural organic matter (NOM) seriously challenges the drinking water supply. It typically exists as complex organic substances generated in the natural water ecosystem as part of hydrologic, biological, and geological cycles. The significant variation, composition, and abundance of NOM in natural water or wastewater necessitate the implementation of robust and adaptive technologies, particularly in addressing even more stringent standards of drinking water supply or treated water discharge. Coagulation is one of the most common processes for water and wastewater treatments. It is highly desirable to treat feed containing NOM because it prevents the disinfection of by-products formation. Therefore, current dynamics of NOM in terms of varying compositions and concentrations demand improvement in handling the coagulation process through optimization of operational parameters (dosing and the control of pH), application of novel and more effective coagulants, and as a combination with other processes through process intensification. This review provides a comprehensive analysis of recent literature on developments of coagulation for NOM removal. The coagulants are grouped systematically and assessed. Next, enhanced coagulation via process intensification with other processes (membrane filtration, oxidation, adsorption, and ion exchange) is discussed. Lastly, the future outlook on research direction on sustainable coagulation process is listed to support circular and bioeconomy.